EFFECTIVENESS OF SELF INSTRUCTIONAL MODULE ON KNOWLEDGE OF POST OPERATIVE SELF CARE FOR MOTHERS UNDERGOING ELECTIVE CAESAREAN SECTION IN SELECTED HOSPITALS, MANGALORE - Rajan, Elizabeth; Nayak, Sabitha (Journal of Health and Allied Sciences NU, 2014)
The study was conducted on Effectiveness of self instructional module on knowledge of post operative self care for mothers undergoing elective caesarean section in selected hospitals, Mangalore. The research design was a one group pre test post test design which was a pre experimental research design. 40 mothers undergoing elective caesarean section by purposive sampling.The pretest knowledge questionnaire was administered to the mothers two days prior to caesarean section, followed by a self instructional module on post operative self care. Post test was conducted after 5 days using the same tool. The collected data were analyzed using descriptive and inferential statistics. The mean knowledge score was 14.98 whereas maximum possible score was 30. Among the 11 areas, the mean percentage knowledge score in the area of caesarean section and self care was 77.50% bladder and bowel care was 60% breast feeding was 58.40% diet was 52.50% pain management was 47.50% post operative complications and home care was 46% baby care was 44.33% early ambulation and exercise was 44% perineal hygiene was 41% wound care was 40.67% and deep breathing and coughing was 40.67%.The 't' value showed significant in the post test ('t' calculated value of pretest and post test knowledge scores = 18.000, p<0.001) which showed that self-instructional module was effective in improving the knowledge of mothers on post operative self care after caesarian section.There was significant association between the level of knowledge and demographic variables namely age parity, education, occupation, monthly income, exposure to health awareness and history of caesarean section.
Keywords: Caesarean section; mothers; post operative self care; self instructional module